Characterizing Land Use Systems within Awoja Watershed - Aben, Charles; Okiror, John J.; Agea, Jacob G.; Hansen, Esbern F. (Energy and Earth Science, 2019)
This manuscript analyses trends in land use changes in Awoja Watershed with the aim of exploring the underlying causes of degradation in this watershed within the context of frequent draughts and floods. Changing trends of land use characteristics were used as indicators of ineffectiveness of control of access to resource use in the watershed. The study was carried out in the districts of Katakwi, Amuria and Sorotiin Eastern Uganda where the watershed is experiencing increasing trends of degradation despite the presence of elaborate watershed management institutions. The study used Remote Sensing, and focus group discussions to acquire relevant data on land use changes and their perceived causes.Perceptions of respondents on the effectiveness of the local governance processes were generated. The findings show increase in built-up areas from 0.21% between 1986-1996; to 3.28 between 2006 and 2016 and a notable decrease in forest cover from 107.48 Km2 in 1,986 to 6.94 Km2 by 2016. The results also show a dramatic increase in small scale farming area from 629.44 Km2 to 2,376.64 Km2 from 1986-2016 while the area of wetland reduced from 2,810.47 Km2 to 1,355 Km2over the same period. Results from focus group discussions revealed that although climatic and demographic factors were responsible for land use changes in Awoja, control of access to natural resources was inadequate to stop degradation. Climatic factors mentioned included increased frequency of floods and draughts that were perceived to have been responsible for changes in vegetation cover, water levels and infrastructure. Socio economic factors driving the changes in land use included increased cultivation of wetlands and communal land, increased sale of fuel wood, charcoal and sand, increased migration of cattle herders into the watershed during draughts and out of it during floods and increased fishing. While climatic factors were important, socio political factors such as displacements of communities, resettlements in the fragile environment brought about by government efforts to demarcate wetlands and wild life conservation areas were cited as drivers of degradation. The study concludes that besides climatic factors, inadequate management of access to resources was contributing to degradation of the watershed.
Keywords: watershed management; land use changes; climate change